Profiling of Phytochemicals in the Leaves of Asystasia gangetica (L) T. Anderson using GC-MS and HPLC Analysis - Odion, Emmanuel Eimiomodebheki; Elakhe, Deborah Evelyn; Ambe, Daniel Akpe-Efiak; Osigwe, Chinyelu Clementina; Odiete, Eravweroso Congrat (Journal of Nepal Chemical Society, 2024)
Asystasia gangetica is a perennial herb that has naturalized in Africa and Asia, where it is use in treatment of varying ailments such as lowering of blood sugar, sexually transmitted infections, reduce swelling and ear disease. The presence of phytochemicals in this plant may be responsible for its acclaimed effects. This study aims to identify the phytoconstituents in the leaves of Asystasia gangetica. Preliminary phytochemical screening was achieved by standard methods, GC-MS and HPLC analyses were utilized to determine volatile and non-volatile compounds. Phytochemicals identified include alkaloids, tannins, steroids, saponins, flavonoids, and glycosides. GC-MS analysis identified twenty-eight compounds with Z-(13,14-Epoxy)tetradec-11-en-1-olacetate (8.72 %); Octadecane, 1-(ethenyloxy)- (8.77 %); Cycloheptano[d]imidazolidine, 1,3- (9.81 %); cis-Vaccenic acid (10.20 %); 15-Hydroxypentadecanoic acid (11.94 %) as the prominent compounds and HPLC evaluation reported the most prominent compounds such as proanthocyanidin (6.69 %), flavone (7.51 %), spartein (7.64 %), aphylidine (10.33 %) and cyanogenic glycoside (10.51 %) respectively. Identification of these compounds with documented evidence of pharmacological activities, thus validate the use of Asystasia gangetica, in many disease conditions.